Minimally Invasive Tubular Lumbar Discectomy Versus Conventional Open Lumbar Discectomy: An Observational Study From the Canadian Spine Outcomes and Research Network. Issue 5 (June 2023) - Evaniew, Nathan; Bogle, Andrew; Soroceanu, Alex; Jacobs, W. Bradley; Cho, Roger; Fisher, Charles G.; Rampersaud, Y. Raja; Weber, Michael H.; Finkelstein, Joel A.; Attabib, Najmedden; Kelly, Adrienne; Stratton, Alexandra; et al.
Study Design: Retrospective cohort study. Objective: We evaluated the effectiveness of minimally invasive (MIS) tubular discectomy in comparison to conventional open surgery among patients enrolled in the Canadian Spine Outcomes and Research Network (CSORN). Methods: We performed an observational analysis of data that was prospectively collected. We implemented Minimum Clinically Important Differences (MCIDs), and we adjusted for potential confounders with multiple logistic regression. Adverse events were collected according to the Spinal Adverse Events Severity (SAVES) protocol. Results: Three hundred thirty-nine (62%) patients underwent MIS tubular discectomy and 211 (38%) underwent conventional open discectomy. There were no significant differences between groups for improvement of leg pain and disability, but the MIS technique was associated with reduced odds of achieving the MCID for back pain (OR 0.66, 95% CI 0.44 to 0.99, P < 0.05). We identified statistically significant differences in favor of MIS for each of operating time (MIS mean (SD) 72.2 minutes (30.0) vs open 93.5 (40.9)), estimated blood loss (MIS 37.9 mL (36.7) vs open 76.8 (71.4)), length of stay in hospital (MIS 73% same-day discharge vs open 40%), rates of incidental durotomy (MIS 4% vs open 8%), and wound-related complications (MIS 3% vs open 9%); but not for overall rates of reoperation. Conclusions: Open and MIS techniques yielded similar improvements of leg pain and disability at up to 12 months of follow-up, but MIS patients were less likely to experience improvement of associated back pain. Small differences favored MIS for operating time, blood loss, and adverse events but may have limited clinical importance.